The effectiveness of good reward system towards employee's motivation / Nur Zailiaton Salleh - Salleh, Nur Zailiaton (2013)
The researcher has studied about the effectiveness of good reward system towards employee's motivation at Muda Agricultural Development Authority (MADA). Good reward systems were studied in attempt to find the factors that influence the employee's motivation. The objectives of this study were to identify the factors that influence employee's motivation, to examine the good reward system towards employee's motivation and to determine the level of job motivation among employees. A total of 70 support staffs at various stages of education level, ages ranged and years of service participated in this study. The instrument used was a questionnaire. The questionnaire solicited demographic background of the respondent for Section A. Section B was to identify the factors that influence employee's motivation, Section C was to examine the good reward system towards employee's motivation and Section D to determine the level of job motivation among employees. Questionnaires were distributed to the respondents and 100% respondents have returned the completed questionnaires. Data was analyzed using SPSS version 20.0 for frequencies, mean and standard deviation. Based on the findings, the researcher has found that job recognition was a good reward system towards employee's motivation. This is because from the analysis, it shown that when employees and their work are valued, their satisfaction and productivity rises, and they are motivated to maintain or improve their good work. As a conclusion, the effectiveness of good reward system can give a lot of positive effects towards employee's motivation. Compensation, job recognition and employee benefits can influence employees to increase their motivation towards their job.